The Florida Natural Resources Leadership Institute - Roy R. Carriker (EDIS)
FE-667, a 6-page fact sheet by Roy R. Carriker, provides an introduction to the FNRLI. It describes the structure and the content of the curriculum, profiles the natural resource leaders for whom the program is designed and introduces the faculty and staff. Published by the UF Department of Food and Resource Economics, September 2006.